Development, characterization, antioxidant and hepatoprotective properties of poly(Ɛ-caprolactone) nanoparticles loaded with a neuroprotective fraction of Hypericum perforatum - Oliveira, Ana Isabel (2019)
Quercetin and biapigenin are antioxidant and neuroprotective compounds present in Hypericum perforatum, with potential application in neurodegenerative diseases. Quercetin has shown to have excellent antioxidant activities. Biapigenin possesses a distinctive mechanism of action, preventing the onset of calcium deregulation and mitochondrial dysfunction. The main aim of this study was to establish a new delivery system encapsulating H. perforatum neuroprotective fraction, isolated from it,containing quercetin and biapigenin into poly(Ɛ-caprolactone) (PCL) nanoparticles. It also aimed to study its hepatoprotective potential. Different formulation parameters were optimized, resulting in a stable formulation of polymer:compounds ratio 1:0.1 with a mean particle size of 185nm, zeta potential around -20mV and association efficiency close to 100%. Compounds in vitro release, under physiological conditions, showed an initial burst followed by a sustained release. The antioxidant functional properties of these compounds were not altered by encapsulation. PCL-loaded nanoparticles protected HepG2 cells from intrinsic compound toxicity at high concentrations. Depending on the incubation regimen, quercetin-biapigenin PCL-loaded nanoparticles or free compounds were more effective in protecting HepG2 cells against tert-butylhydroperoxide-induced toxicity. This is the first report of the encapsulation of a quercetin-biapigenin mixture in a polymeric matrix, specifically, in PCL, with synergic anti-oxidant and hepatoprotective effects.